RELATIONSHIP BETWEEN MULTIPLE INTELLIGENCE, SELF-ESTEEM AND TEACHER COMPETENCY AMONG SECONDARY SCHOOL TEACHERS - Sahay, Manjita (PEOPLE: International Journal of Social Sciences, 2019)
The objective of the research study was to find out whether there is any existing relationship between Multiple Intelligence, Self-Esteem and Teacher Competency of Secondary School Teachers of Patna District, Bihar, India. The methodology applied were the survey method with a self-constructed and standardised validated test. The tests utilized were i) The Multiple Intelligence Test a standardised test by Howard Gardner.2) Teacher Effectiveness scale constructed by researcher.3) Self-Esteem Test –A standardised test by M.J. Sorensen. These tests were administered to 500 randomly selected Secondary School Teachers working in schools of Patna, Bihar, India. The data were analysed by employing Mean, Standard Deviation, t-test, Product moment Coefficient of Correlation, ANOVA, Regression, Chi-Square Test and Mann Whitney Test. The findings of the study were:1)There is no significant difference between Male & Female Secondary School Teachers in their Teacher Competency but there is significant difference between Male & Female Teachers in their Multiple Intelligence.2)There is no significant difference between Govt. &Pvt. Secondary School Teachers in their Multiple Intelligence but there is a significant difference between Govt. & Pvt. Secondary School Teachers in their Teacher Competency as well as Self-Esteem.3) There is a significant positive relationship between Multiple Intelligence and Teacher Competency of Secondary School Teachers.4)There is a significant positive relationship between Multiple Intelligence and Self-esteem of Secondary School Teachers. 5) There is a significant positive relationship between Teacher Competency and Self-esteem of Secondary School Teachers.